Hubungan antara Kematangan Emosi dan Religiusitas dengan Penyesuaian Diri pada Mahasiswa Perantau di Asrama Daerah Mahasiswa Yogyakarta - Yulieta Sari (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2021)
Overseas students are often faced with various changes that require them to be able to adjust to a new environment. However, there are still many overseas students who have difficulty adjusting themselves. One of the factors that influence self-adjustment is emotional maturity and religiosity. This study aims to determine the relationship between emotional maturity and religiosity with adjustment in overseas students. This research was conducted on overseas students aged 18 to 25 years and were overseas students who lived in dormitories in Kalimantan, Nusa Tenggara and Bali. The sample of this study was 108 overseas students who were taken using cluster random sampling technique. The data were collected using a self-adjustment scale, the emotional maturity scale, and the religiosity scale. The statistical analysis technique used is multiple regression techniques. The results of the analysis showed that there was a relationship between emotional maturity and religiosity with self-adjustment in migrant students with a significance value of 0.000 (P <0.05). This means that the higher the emotional maturity and individual religiosity, the higher the adjustment. Emotional maturity and religiosity together contribute effectively to self-adjustment of 47.4%. Emotional maturity contribute effectively to self-adjustment of 45.1%, while religiosity made an effective contribution to self-adjustment of 2.3%.